2004
DOI: 10.2134/jeq2004.2306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytase Addition to Poultry Diets on Phosphorus Forms and Solubility in Litters and Amended Soils

Abstract: Diet modification to decrease phosphorus (P) concentration in animal feeds and manures can reduce surpluses of manure P in areas of intensive animal production. We generated turkey and broiler litters from two and three flock trials, respectively, using diets that ranged from "high" to "low" in non-phytate phosphorus (NPP) and some of which contained feed additives such as phytase. Phosphorus forms in selected litters were analyzed by sequential chemical fractionation and solution (31)P nuclear magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 34 publications
11
83
0
2
Order By: Relevance
“…This finding supports previous work where analysis of excreta from broilers fed diets containing various cultivars of barley revealed that only trace amounts of phytate P were excreted, irrespective of the phytate P concentration of the initial feed (Leytem et al, 2007). However, as the diets in the studies by Maguire et al (2004) and Leytem et al (2006) also contained appreciable amounts of inorganic Ca and P, it could be expected that differences in the proportion of phytate P in the excreta were due to the detrimental effects of these minerals on intestinal phytate P hydrolysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports previous work where analysis of excreta from broilers fed diets containing various cultivars of barley revealed that only trace amounts of phytate P were excreted, irrespective of the phytate P concentration of the initial feed (Leytem et al, 2007). However, as the diets in the studies by Maguire et al (2004) and Leytem et al (2006) also contained appreciable amounts of inorganic Ca and P, it could be expected that differences in the proportion of phytate P in the excreta were due to the detrimental effects of these minerals on intestinal phytate P hydrolysis.…”
Section: Discussionsupporting
confidence: 91%
“…Maguire et al (2004) reported that litter from birds fed maize-based diets contained 0.26-0.56 of P as phytate P, while concentrations in manure from layers fed maize-based diets ranged from 0.35 to 0.80 of total P (Leytem et al, 2006). Based on these findings, it was expected that there would be reasonable concentrations of phytate P in the excreta in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…' 6 Poultry litter (feces mixed with bedding material) and manure can contain high concentrations of phytate. For example, Maguire et al 4 reported that litter from broilers and turkeys fed corn-based diets contained between 26 and 56% of total P as phytate, while Leytem et al 17 reported that phytate concentrations in manures from layers fed corn based diets ranged from 35 to 80% of total P. However, recent analysis of pigs fed diets containing various cultivars of barley revealed that only trace amounts of phytate were excreted, irrespective of the phytate concentration of the initial feed." Clearly, our understanding of the metabolism of phytate in monogamic animals is limited and information is needed on the P composition of feces obtained from a wide range of animals and diets.…”
Section: Introductionmentioning
confidence: 99%
“…Solution 31 P NMR spectroscopy has been used to quantify the phosphorus composition of a wide variety of manures (Leinweber et al, 1997;1,eytem et al, 2004;Maguire et al, 2004;Turner and Leytem, 2004;McGrath et al, 2005). These studies indicate that manure phosphorus is predominately inorganic phosphate, followed in descending order by phosphate monoesters, phosphate diesters (nucleic acids and phospholipid), pyrophosphates and, in some cases, phosphonates.…”
Section: Phosphorus Composition Of Animal Manuresmentioning
confidence: 99%
“…Therefore, after 150 days of storage, there was no significant difference in myo-inositol hexakisphosphate concentrations in swine manures from the two diets. Maguire et al (2004) grew three flocks of broilers and two flocks of turkeys on the same bed of litter using diets that were 'high' and 'low' in non-phytate phosphorus with and without phytase additions. Concentrations of myo-inositol hexakisphosphate in both broiler and turkey litters from diets that included phytase were consistently lower than in litters from equivalent non-phytase diets ( (2005) analysed turkey manure and broiler litter samples from diets with and without phytase using X-ray absorption near-edge structure spectroscopy.…”
Section: Feeding Microbial Phytase As a Supplementmentioning
confidence: 99%